MAKSIMISASI PENDAPATAN NELAYAN PANCING ULUR DI DESA TETE B KABUPATEN TOJO UNA-UNA - Dafina Howara (Universitas Tadulako, 2014)
This paper examine Fishermen Fishing Revenue Maximization of War In the village of Tete B Tojo Una-Una. Data analysis using LINDO analysis. The analysis showed that the maximum earned income fishermen fishing village stretching in Tete B of Rp 40,036,480.00 with a total production of 15 667 kg produced for a period of catch in a month. Resources used to obtain the maximum income is as much as 4856.67 liters of gasoline, lubricants or oils as much as 47 liters, ice packs as much as 3446.67, and cigarette consumption as much as Rp 6,000,333.33 1096.67 wrap. If fishermen are utilizing the maximum revenue production inputs can be obtained by Rp 40,036,480.00. Key Words : Fishing rod stretching, revenue maximization, and Lindo,